Generality of reduplication and its role in the typological classification of languages (Eurasian Research Bulletin, 2022)
Word formation is characteristic of the systems of all languages, because the word formation process itself is constantly operating and the word formation means themselves are dynamically evolving. On this basis, new lexical units are created and the vocabulary of a particular language is enriched. The existence of word formation in the systems of different languages testifies to the typological commonality of this phenomenon.